(untitled) (Research, Society and Development, 2021)
This article intends to reflect on the leading role of the Movement of People Affected by Dams (MAB) in the dynamics of development, based on the sustainability category. The methodology adopted was a literature review, analysis of public documents and a case study of the experiences carried out by the MAB, in the set of actions to confront and resist the neoliberal situation adopted from the 1990s onwards. social conflicts involving the implementation of dams gain more and more space in the media and there is an evolution in MAB’s performance, the “risk assessment” model of the 80s and 90s persists when it comes to involuntary resettlements. This is because the theoretical-conceptual instrument naturalizes populations, representing them as obstacles to progress and does not treat them as social actors capable of discussing rights and interests.